Development of Superior Human Resources (HR) In Facing The Era of Globalization - Ferdy Leuhery (Return : Study of Management, Economic and Bussines, 2023)
The existence of the world today is full of openness, the world seems to be unified or known as globalization. As a consequence of the era of globalization, is the high level of competition and the challenges it poses. Like it or not, this is a reality that every citizen must face. The fundamental question of this reality is whether humans are able and ready to be conditioned as resources of social transformation or anticipated resources as actors of development. One of the efforts to anticipate it is to create various superior human resources who have the ability to do something for their nation. The method used in this study is descriptive analytic, which describes phenomena that exist or are happening then analyzed with theory and produce a solution (solution). The results of this study show that the urgency of human resource development is a key factor in winning global competition, which has consequences for increasingly fierce competition amid uncertainty, this strategic step deserves full support from all stakeholders. Strengthening human resources towards superior humans has a close correlation with increasing work productivity, in winning competition amid rapid changes in the world of business, political economy and culture in the midst of world turmoil that is increasingly competitive and developing.